Numerosity comparison, cognitive strategies, and general cognitive functioning in older people - Słupczewski, Jakub; Gut, Małgorzata; Matulewski, Jacek; Tarnowski, Adam (Frontiers in Psychology, 2024)
Studies have shown age-related differences in numerical cognition, for example, in the level of numerosity comparison ability. Moreover, some studies point out individual differences in the cognitive strategies employed during the performance of numerosity comparison tasks and reveal that they are related to the aging process. One probable cause of these differences is the level of cognitive functioning. The aim of our study was to determine the relationships among numerosity comparison ability, the cognitive strategies utilised in the performance of numerosity comparison tasks and the general cognitive functioning in older people. Forty-seven elderly people participated in the study. The participants were examined using overall cognitive functioning scales and computerised numerosity comparison task. The results showed many correlations between the participants' level of cognitive functioning and the percent of correct responses (PCR) and response time (RT) during numerosity comparison, as well as with the cognitive strategies applied by the participants. Task correctness was positively related to the level of performance in the attention and executive function tasks. In contrast, the long-term memory resources index and visuospatial skills level were negatively correlated with RT regarding numerosity comparison task performance. The level of long-term memory resources was also positively associated with the frequency of use of more complex cognitive strategies. Series of regression analyses showed that both the level of general cognitive functioning and the cognitive strategies employed by participants in numerosity comparison can explain 9-21 percent of the variance in the obtained results. In summary, these results showed significant relationships between the level of cognitive functioning and proficiency in numerosity comparison measured in older people. Moreover, it has been shown that cognitive resources level is related to the strategies utilised by older people, which indicates the potential application for cognitive strategy examinations in the development of new diagnostic tools.